2010
DOI: 10.1111/j.1365-2834.2010.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of workplace incivility and empowerment on newly-graduated nurses’ organizational commitment

Abstract: Without specific strategies in place to combat incivility and disempowerment in the workplace, attempts to prevent further organizational attrition of new members may be futile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(160 citation statements)
references
References 57 publications
9
143
0
8
Order By: Relevance
“…The majority of nursing faculty were satisfied with their jobs and felt empowered in their workplaces. Smith, Andrusyszyn, and Laschinger (2010) found the integrated model was supported by the results of a study in which SE, PE, and workplace incivility were predictors of affective commitment in new graduate nurses.…”
Section: Structural and Psychological Empowerment In Nursingsupporting
confidence: 59%
“…The majority of nursing faculty were satisfied with their jobs and felt empowered in their workplaces. Smith, Andrusyszyn, and Laschinger (2010) found the integrated model was supported by the results of a study in which SE, PE, and workplace incivility were predictors of affective commitment in new graduate nurses.…”
Section: Structural and Psychological Empowerment In Nursingsupporting
confidence: 59%
“…Research has shown that SE and PE can be linked to job commitment (Smith, Andrusyszyn, and Laschinger, 2010), decreased job stress and burnout (O'Brien, 2011), job satisfaction and staff retention . It is therefore relevant that the academic organization in Rwanda take the opportunity to gain an understanding of the importance of empowerment components, and the potential positive educational outcomes for faculty, students, nursing staff, and clients in the practice setting.…”
Section: Resultsmentioning
confidence: 99%
“…Job satisfaction and job commitment were positively associated with perceived SE and PE empowerment with public health nurses (Chang, Lui, & Yen, 2008), nurse educators , staff nurses (Laschinger, Finegan, & Wilk, 2009;Smith, Andrusyszyn, & Laschinger, 2010). Job strain and job burnout were reduced when nursing staff was structurally and psychologically empowered in their professional positions (Laschinger, Finegan, Shamain, & Wilk, 2001;O'Brien, 2011).…”
Section: Structural and Psychological Empowerment In Nursingmentioning
confidence: 99%
“…Learning the skilled knowledge of the practice requires tolerance for error, so a healthy work environment characterized by respect and civility which is supportive to young practitioners is a prerequisite for learning how to be an excellent nurse [12,13] . The challenge for nurse managers is how to connect nurses and patients in relationships that ensure the best care for patients and maximum experiential learning for the nurse while protecting the safety of both [11] .…”
Section: Experiential Learningmentioning
confidence: 99%